Energy Management Strategy of Control Parameter Adjustment for Extended-Range Electric Tractors - Liyou, Xu; Junjiang, Zhang; Mengnan, Liu; Zhili, Zhou; Chengqiang, Liu (International Journal of Agricultural and Biological Engineering, 2017)
It is difficult to make full use of the electrical energy of the power battery for extended-range electric tractors because the battery’s state of charge may be relatively high at the end of the running mileage. To address this situation, this paper aimed to study the control parameter adjustment in relation to the power battery’s electrical consumption and the diesel engine’s fuel consumption energy management strategy. Based on the AVL-Cruise simulation platform, the vehicle model of the tractor was established, and the control module of AVL-Cruise was used to compile the energy management strategy. In order to verify the superiority of the proposed strategy, the contrast strategy was employed in terms of the diesel engine start and stop control plus fixed point energy management strategy (FPEMS). The applicability of the proposed strategy was tested through continuous transfer operation and the small area deep loosening operation. The simulation results show that the proposed strategy was of good applicability. Compared with the FPEMS, the fuel consumption reduced significantly, and the electrical consumption of the power battery increased obviously. Keywords: extended-range electric tractor, parameter adjustment, energy management strategy, simulation analysis DOI: 10.25165/j.ijabe.20171005.2692 Citation: Xu L Y, Zhang J J, Liu M N, Zhou Z L, Liu C Q. Control algorithm and energy management strategy for extended range electric tractors. Int J Agric & Biol Eng, 2017; 10(5): 35–44.